Gender Differences in Skeletal Muscle Substrate Metabolism – Molecular Mechanisms and Insulin Sensitivity - Lundsgaard, Anne-Marie; Kiens, Bente (Frontiers in Endocrinology, 2014)
It has become increasingly apparent that substrate metabolism is subject to gender specific regulation, and the aim of this review is to outline the available evidence of molecular gender differences in glucose and lipid metabolism of skeletal muscle. Female sex has been suggested to have a favorable effect on glucose homeostasis, and the available evidence from hyperinsulinemic-euglycemic clamp studies is summarized to delineate whether there is a gender difference in whole body insulin sensitivity and in particular insulin-stimulated glucose uptake of skeletal muscle. Whether an eventual higher insulin sensitivity of female skeletal muscle can be related to gender specific regulation of molecular metabolism will be topic for discussion. Gender differences in muscle fiber type distribution and substrate availability to and in skeletal muscle are highly relevant for substrate metabolism in men and women. In particular, the molecular machinery for glucose and fatty acid oxidative and storage capacities in skeletal muscle and its implications for substrate utilization during metabolic situations of daily living are discussed, emphasizing their relevance for substrate choice in the fed and fasted state, and during periods of physical activity and recovery. Together, handling of carbohydrate and lipids and regulation of their utilization in skeletal muscle have implications for whole body glucose homeostasis in men and women. 17-β estradiol is the most important female sex hormone, and the identification of estradiol receptors in skeletal muscle has opened for a role in regulation of substrate metabolism. Also, higher levels of circulating adipokines as adiponectin and leptin in women and their implications for muscle metabolism will be considered.